2019
DOI: 10.3390/microorganisms7060173
|View full text |Cite
|
Sign up to set email alerts
|

The Revival of the Battle between David and Goliath in the Enteric Viruses and Microbiota Struggle: Potential Implication for Celiac Disease

Abstract: The human gut is inhabited by overcrowded prokaryotic communities, a major component of which is the virome, comprised of viruses, bacteriophages, archaea, eukaryotes and bacteria. The virome is required for luminal homeostasis and, by their lytic or synergic capacities, they can regulate the microbial community structure and activity. Dysbiosis is associated with numerous chronic human diseases. Since the virome can impact microbial genetics and behavior, understanding its biology, composition, cellular cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…Historically, viruses have been viewed as threatening because they were best known for causing disease. While their full role in human health is still mostly unknown [26,27], we are beginning to understand the associations between the enteric and respiratory virome and acute and chronic human diseases [27][28][29][30], and a recent study showed that bacteriophages modulate bacteria communities in the gut [31]. The majority of viruses and virusderived genetic elements appear to be benign; some may even be essential for good health if the hygiene hypothesis [32] applies to viruses as well as bacteria.…”
Section: Healthy Viromementioning
confidence: 99%
“…Historically, viruses have been viewed as threatening because they were best known for causing disease. While their full role in human health is still mostly unknown [26,27], we are beginning to understand the associations between the enteric and respiratory virome and acute and chronic human diseases [27][28][29][30], and a recent study showed that bacteriophages modulate bacteria communities in the gut [31]. The majority of viruses and virusderived genetic elements appear to be benign; some may even be essential for good health if the hygiene hypothesis [32] applies to viruses as well as bacteria.…”
Section: Healthy Viromementioning
confidence: 99%
“…The human microbiome has come to be known as a key player in the modulation of its host's immunity and thought to take part in the pathogenesis of various chronic diseases and autoimmune conditions. The virome however, which includes the gastrointestinal presence of viruses and their interaction with the host have been less explored and only recently data has been emerging regarding intestinal luminal viruses and bacteriophages [ 51 ]. The mechanism by which viruses interact with the host is via penetration and integration of their genetic material into the host genome [ 52 ].…”
Section: Interactions Between Viruses and The Human Gutmentioning
confidence: 99%
“…The extra-and intra-luminal sources of mTG were summarized recently [7,[12][13][14]. Table 1 updates those sources, adding "viral transglutaminase" [15][16][17][18]. Interestingly, when studying the amino acid sequences of the recently described prevotella-specific megaphages, a transglutaminase-like sequence was found in human and several animal stool samples when aligned with mTG amino acid sequence (Ramesh Ajay unpublished personal communications) [19].…”
Section: Enteric Luminal Sources Of Microbial Transglutaminasementioning
confidence: 99%
“…Microbiome [7,[12][13][14]24,25] Dysbiome [7,[12][13][14]24,25] Yeasts [34][35][36] Fungi [37,38] Viruses [15][16][17][18]…”
Section: Intra-intestinalmentioning
confidence: 99%